How does air pollution affect urban settlement of the floating population in China? New evidence from a push-pull migration analysis - Zhao, Zhihao; Lao, Xin; Gu, Hengyu; Yu, Hanchen; Lei, Ping (BMC public health, 2021)
Background Severe air pollution in China threatens human health, and its negative impact decreases the urban settlement intentions of migrants in destination cities. We establish a comprehensive framework based on the push-pull migration model to investigate this phenomenon. Methods We employ a logistic model to analyze air pollution's impact on the settlement intentions of the floating population based on the CMDS 2017 in China, combining the city-level socioeconomic variables with the individual-level variables. Results Our results show that the annual average concentration of PM2.5 increases by 1 unit and that the probability of migrants' settlement intentions will decrease by 8.7%. Using a heterogeneity analysis, we find that the following migrant groups are more sensitive to air pollution: males, people over 30 years old, less educated people, and migrants with nonagricultural hukou. With every 1 unit increase in PM2.5, each group's settlement intentions decrease by 13.2, 16.7, 16.9, and 12.6%, respectively. Conclusions Our results are consistent with existing studies. This study discovers that both external environment and internal factors influence migrants' settlement intentions. Specifically, the differences in population sizes, economic development levels, public services, infrastructure conditions, and environmental regulations between cities play a significant role in migration decisions. We also confirm heterogeneous sensitivities to air pollution of different migrant subgroups in terms of individual characteristics, family factors, migration features, social and economic attributes. Keywords: Air pollution, Settlement intentions, Floating population, Heterogeneity, Push-pull migration model